Doing academic writing differently: a feminist bricolage. Issue 5 (28th July 2016) - Handforth, Rachel; Taylor, Carol A.
ABSTRACT: This article emerged as the product of a collaboration between two individuals at different stages of our academic careers, one a beginning researcher and the other a senior academic. Written as an experimental bricolage, the article weaves together two main threads to chart our engagements with feminist research and with writing practices, both of which we envisage as forms of feminist praxis. The red thread explores feminist research as a continuous accomplishment in which becoming-feminist is enacted through our different research narratives. The green thread employs diffraction, as an experimental practice to undo the normalised practices of academic writing by weaving together various kinds of texts. In its entangled quilting of the red and green threads, the article foregrounds bricolage as an experimental feminist praxis of doing collaborative writing differently.